PHYSICAL ACTIVITY AND FREE TIME IN THE LIFE OF STUDENT YOUTH - Borysevych, L. V. (Rehabilitation and Recreation, 2022)
The article is aimed at highlighting the problem of organizing and spending free time. After all, in modern conditions most of their time our young people, not only young people, spend, mainly in a sitting position, active recreation has changed to passive. There is a tendency to reduce the interest of young people in physical culture and sports. Young people are more immersed in gadgets and spend most of their free time on social networks rather than in or stadiums or gyms. The physical activity of the modern student wants to be better. People became indifferent to themselves and their health, thansks to the benefists of civilization, there was a self – liberation of man from self – effort, resulting in the destruction of the body`s defenses. The results of the leisure time studyand the way of student youth`s leisuregive us some information about their lifestyle, interests and priorities, including their understanding of the healthvalue and the need for physical activity. As we can see not everyone has an understanding of how important the quality of leisure time and the benefits of physical activity. After all, muscle movements have a positive impact on the physiological activity of all body systems, they strengthen the immune system, stimulate mental activity, as well as provide social activity. A person`s activity preserves his youth for a long time, increasing his creative potential, and not allowing himself to be lazy. The results ofther research have shown that due to the benefist of civilization, there is a tendency to reduce the activity of leisure time among student youth, unfortunately, most of it is passive and is performed in front of various gadgets. There is also the problem of young people`s inability to organize their free time so that it can be used to their advantage. Students prefer to communicate with friends, and often this communication takes plase on social networks.